Case report Isolated Primary Intra-uterine Hydatid Cyst – Benghazi, Libya - M. K., Farid, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Hydatid cysts in the genital tract are rare and the occurrence in the uterus is an extreme rarity.Differentiation between hydatid cyst and malignant disease of the related organ is of greatimportance. We report a case of hydatid cyst in the uterus.